A Modulated Model Predictive Control Based on the Vector Modulation for Tri-Port DC-DC Converter in Photovoltaic-Battery Hybrid Power Systems - Feng, Qihui; Xu, Yutao; Tan, Zukui; Zhang, Chao; Chen, Dunhui; Yuan, Xufeng (2023 IEEE International Conference on Power Science and Technology (ICPST), 2023)
The paper presents a new modulated model predictive control (MMPC) method based on the vector analysis for tri-port DC-DC Converter in photovoltaic-battery hybrid power systems. The proposed MMPC method uses three fundamental vectors to calculate the optimal switching sequence to minimize the error vector. It can significantly minimize voltage ripples while retaining the nonlinear and dynamic performance of conventional MPC methods. Simulation results on a PLECS simulation are provided to validate the proposed control strategy. Compared to the conventional MPC method, the proposed method can achieve significant current and voltage ripple reduction and excellent dynamic performance with smoothing mode switching. Meanwhile, the proposed MMPC can achieve fixed switching frequency control to simplify the filter design. 1